GEREJA KATOLIK ST.TERESIA KOTA JAMBI 1935-2011 - Aulia Kristina, Ulul Azmi (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2019)
AbstractThe Santa Teresia Jambi Parish Church experienced cultural acculturation and inclusion as outlined in the church building, among others: walls, pillars, roofs, towers and ornaments supporting other worship activities, then the development of the Church of Santa Teresia during the period 1935-2011 can be seen the appearance of church buildings, number of congregations and activities carried out in the church. The church is located on Jalan Raden Mataher, so it can be concluded that the diversity of cultures and building forms of the Catholic Church is not a place of worship but also can do social activities or others. Keywords:Socio-Culture, History, Church of Santa Teresia Jambi. AbstrakGereja Paroki Santa Teresia Jambi mengalami Akulturasi dan inkukturasi budaya yang dituangkan pada bangunan gereja antara lain: dinding, tiang, penyangga, atap, menara dan ornament-ornamen penunjang kegiatan peribadatan lainnya, selanjutnya perkembangan Gereja Paroki Santa Teresia selama priode 1935-2011 dapat dilihat dari penampilan bangunan gereja, jumlah jemaat maupun kegiatan yang dilakukan di gereja. Gereja yang terletak di Jalan Raden Mataher, sehingga dapat disimpulkan bahwa keragaman budaya dan bentuk bangunan Gereja Katolik  bukan sebagai tempat peribadatan tetapi juga bias melakukan kegiatan sosial yang ataupun yang lain. Kata Kunci: Sosial Budaya, Sejarah, Gereja Santa Teresia Jambi.